Nature-inspired slippery polymer thin film for ice-repellent applications. Issue 3 (2nd September 2021) - Hanh, Vu Thi Hong; Truong, Mai Xuan; Tan, Tu Quang; Nguyen, Thanh-Binh
Abstract : In this study, the authors investigated the anti-icing performance of a hierarchical slippery polymer thin film that is inspired by structures of the lotus leaf and Nepenthes pitcher plant. The polymer solution was mixed with the lubricant at the appropriate concentration to achieve slippery properties. The dry etching method followed by the spin-coating process was used to generate a uniform polymer microstructure on the thin film. The polymer nanostructure was then yielded by an additional plasma-etching method using carbon tetrafluoride (CF4 ) gas. The anti-icing efficiency was then compared with that of the non-functional samples to demonstrate the advantages of combination in all criteria. Moreover, a theoretical prediction based on the free-energy approach was used to measure the nucleation time at the interface and illustrated good agreement with real-time measurement. The results propose a new and facile approach for outdoor anti-icing applications.